Peningkatan Ekonomi Masyarakat Melalui Pemberdayaan Pangan dari Olahan Pisang di Desa Ranggagata Kecamatan Praya Barat Daya Kabupaten Lombok Tengah - Rohadi Muhammad Rosyidi; Riyadussolihin Ilhami; Aulia Umul Sakinah; Baiq Sinta Galuh Sukma; Baiq Sarifa Wahida; Baiq Shinta Puspa Gading; Hidayatullah Hidayatullah; Jihan Anggryani; Lalu Wahyudi Purnama Hidayat; Nadila Nadila; Septian Juhdi (Jurnal Gema Ngabdi, 2022)
In the era of globalization, there can be a process of widening the gap because of the opportunities in this open economy. Therefore, the main thing that must be prevented in globalization is the emergence of this process. Inequality is a real form of development that can be solved by empowering the community, especially for real weak economic actors. Community empowerment is one of the efforts to facilitate local communities in planning, deciding and managing their resources so that in the end they have the ability and independence in an economically, ecologically and socially sustainable manner. Through this empowerment, the community can develop opportunities to show characteristics and be independent to develop their potential. Ranggagata Village is one of the villages located in Southwest Praya District, Central Lombok Regency, West Nusa Tenggara Province, Indonesia. Ranggagata Village has the potential for banana commodities as raw material for processed products but cannot be utilized by the community itself because there are several inhibiting factors, such as the lack of community innovation in making processed products and the lack of interest in community entrepreneurship. The implementation methods used in this activity are socialization, training and mentoring, and evaluation of activities. The results of the activity showed that the community was able to receive the results of the training well, this was proven by their enthusiasm for participating in the activity from beginning to end. From the results of these activities, it can be concluded that the service activities carried out can provide knowledge and skills to entrepreneurs, especially PKK mothers and housewives to produce products that have high selling value.